KELINDAN ANTARA ‘HAK NEGATIF’ DENGAN ‘HAK POSITIF’ DALAM DISKURSUS HAK ASASI MANUSIA - Mirza Satria Buana (Veritas et Justitia, 2023)
This paper examines the conceptual dichotomy between ‘negative right’ and ‘positive right’ in the current discourse of human rights. The dichotomy has been embedded due to the historical description of generations of human rights, encompassing the civil and political rights that have liberalism influences, to the economic, social, and cultural rights that have socialist influences, and the last generation of rights being the collective and solidarity rights. This paper analyses the dichotomy from the standpoint of the right to development, with some pivotal approaches, including conceptual, case law, and comparative constitutional law approaches. It concludes that the dichotomy can only be used in a teaching and pedagogical setting of human rights, but the dichotomy cannot sustain the test in theoretical-conceptual and practical analyses.